Andreev-Korkin Identity, Saigo Fractional Integration Operator and LipL(α) Functions - Jankov, D.; Pogány, T.K. (Журнал математической физики, анализа, геометрии, 2012)
The Andreev-Korkin identity for the Chebyshev functional is treated by Holder inequality, when the functional consists of LipL(α) functions. The derived upper bound is applied to the so-called Chebyshev-Saigo functional, built by Saigo fractional integral operator - recently introduced by Saxena et al. (R.K. Saxena, J. Ram, J. Daiya, and T.K. Pogany - Integral Tranforms Spec. Funct. 22 (2011), 671-680). К тождеству Андреева-Коркина для функционала Чебышева с функциями применяется неравенство Гёльдера. Полученная верхняя граница применяется к так называемому функционалу Чебышева-Сеге, построенному при помощи оператора Сеге дробного интегрирования, предложенного недавно Р.К. Саксеной и др. (R.K. Saxena, J. Ram, J. Daiya, and T.K. Pogány. - Integral Tranforms Spec. Funct. 22 (2011), 671-680).